Dasca in action: Predictive Modeling series / Nurul Nisa’ Khairol Azmi ... [et al.]. - Khairol Azmi, Nurul Nisa’; Abdul Hadi, Az’lina; Mohd Yusop, Noorezatty; Abdul Wahab, Nurul Aini; Azlan, Nuralina; Md Yasin, Zaitul Anna Melisa; Mohd Razali, Nornadiah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The Predictive Modeling Series is a knowledge-sharing program dedicated to enhancing analysis and modeling skills. It is a collaborative effort between the Special Interest Group Data Science and Predictive Analytics (SIG DASCA) and the College of Computing, Informatics, and Mathematics (KPPIM) at UiTM Negeri Sembilan Seremban Campus. On November 15 and 16, 2023, the Predictive Modeling Series: Time Series Analysis and Forecasting using R programming was successfully conducted at the Library of Tun Abdul Razak, UiTM Negeri Sembilan, Seremban Campus, running from 9:00 am to 4:30 pm as shown in Figure 1. The event attracted a total of 17 beginners and 14 intermediate participants who registered for Course I and Course II of the workshop, respectively. Participants included academicians, industry professionals, and postgraduate students.